2010
DOI: 10.1002/jgm.1451
|View full text |Cite
|
Sign up to set email alerts
|

Combining keratinocyte growth factor transfection into the airways and tracheal occlusion in a fetal sheep model of congenital diaphragmatic hernia

Abstract: Thus, BGTC/DOPE liposomes can mediate efficient KGF transfection into the airways in a fetal sheep model of CDH. Furthermore, combining KGF transfection and TO resulted not only (as did TO alone) in the correction of the CDH-associated lung hypoplasia and decreased RAC, but also in increased SPB synthesis, suggesting a better maturation of the re-growing lung (compared to TO alone). Additional studies are required to further explore the therapeutic potential of such a combined strategy; in particular, studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 59 publications
(79 reference statements)
1
11
0
Order By: Relevance
“…In our study, DHTO lungs demonstrated decreased protein synthesis compared with DH and control lungs, although no specific protein group, such as surfactant proteins, were differentially regulated. This is consistent with human studies demonstrating no difference in surfactant quality or composition in CDH (13) but is inconsistent with animal studies showing the opposite (10,11). With regards to cell hyperplasia, using nitrofen model of CDH, Chapin, et al demonstrated that rat DH lungs contain less DNA than control and that lung Consistent with our gene expression findings (Figure 4), the pathways and processes downregulated by DH were excessively upregulated in DHTO and vice versa ( Figure 8A).…”
Section: Dh Increases Ribosomal Biogenesis Which Is Reversed By Tosupporting
confidence: 58%
See 2 more Smart Citations
“…In our study, DHTO lungs demonstrated decreased protein synthesis compared with DH and control lungs, although no specific protein group, such as surfactant proteins, were differentially regulated. This is consistent with human studies demonstrating no difference in surfactant quality or composition in CDH (13) but is inconsistent with animal studies showing the opposite (10,11). With regards to cell hyperplasia, using nitrofen model of CDH, Chapin, et al demonstrated that rat DH lungs contain less DNA than control and that lung Consistent with our gene expression findings (Figure 4), the pathways and processes downregulated by DH were excessively upregulated in DHTO and vice versa ( Figure 8A).…”
Section: Dh Increases Ribosomal Biogenesis Which Is Reversed By Tosupporting
confidence: 58%
“…DNA content is increased by TO (10). Saada, et al observed epithelial hyperplasia in a sheep model of DHTO (11), and after TO in the rat nitrogen model, there is an increased ratio of alveolar type I to alveolar type II cells (10). Taken together, these findings suggest than one or more epithelial mitogens may be important in the adaptive and maladaptive responses in CDH treated with TO.…”
Section: Dh Increases Ribosomal Biogenesis Which Is Reversed By Tomentioning
confidence: 92%
See 1 more Smart Citation
“…It adds to a small body of studies published in larger animal models (sheep or rabbit) in novel therapies for CDH. In sheep, only transplacental tadalafil has previously been investigated [17,45]. …”
Section: Discussionmentioning
confidence: 99%
“…It also can activate transepithelial ion transport in alveoli and preserves expression of water channels to alleviate high-altitude pulmonary edema (3). An increasing number of studies suggest that KGF protects the lungs from a variety of damage via different mechanisms (4), as well as regulating the development of bronchi during maturation of the fetal lung (5). Nevertheless, the underlying protective mechanism of KGF remains elusive.…”
Section: Introductionmentioning
confidence: 99%